Pertanggungjawaban Hukum Penyedia Jasa Transportasi Darat dalam Kecelakaan Penumpang - Kadek Surya Ganda Ariesta; Ketut Elly Sutrisni; I Gusti Ayu Eviani Yuliantari; Bagus Gede Ari Rama (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the legal liability of land transportation service providers toward passengers who suffer accidents due to negligence, with a primary focus on civil law perspectives while also relating it to consumer protection and administrative law. This research employs a normative legal research method using statutory, conceptual, and factual approaches. The legal materials consist of primary, secondary, and tertiary legal sources, which are analyzed using a descriptive-qualitative method. The findings indicate that the legal liability of land transportation service providers is not merely repressive, but also includes preventive obligations to ensure passenger safety before transportation services are used. From a civil law perspective, the relationship between passengers and service providers is based on a transportation agreement, so accidents caused by negligence may be classified as breach of contract, resulting in an obligation to provide compensation. From the consumer protection perspective, passengers are considered consumers who are entitled to safety and security, while from the administrative law perspective, violations related to operational permits and vehicle roadworthiness may lead to administrative sanctions. The PO Sakhindra Trans accident case demonstrates that failure to fulfill preventive obligations constitutes a major factor in causing accidents and confirms the legal responsibility that must be borne by land transportation service providers.